Heavy metal: Genre? Style? Subculture?. Issue 12 (December 2016) - Gracyk, Theodore
Abstract: Although popular music is increasingly recognized as an important area of inquiry in philosophy of art, many organizing principles have been taken over from other fields without scrutiny. This article selects heavy metal as an example of the value of applying philosophy of criticism to discourse about popular music. Metal is now in its fifth decade, and its combination of longevity and diversity have made it an attractive topic in popular music studies. In accounts of metal by musicologists and social science researches, metal is almost always referred to as a genre of music, and the genre is said to unify diverse metal subcultures, which are associated with diverse styles of metal. An examination of the concepts of genre and subculture as they are typically understood in popular music studies generally, and in metal studies in particular, suggests that they do not function to delineate metal as a unitary category. However, contemporary philosophy of art provides several theoretical principles that provide criteria for identifying a unified genre. The relevant theories are historical definitions of art and Kendall Walton's account of style. Viewed in terms of these philosophical developments, metal should be seen as an evolving assemblage of related styles, only some of which are associated with fans who constitute a subculture. However, it is not a "category" in Walton's sense of that term. Video abstract (click to view)